2004
DOI: 10.1089/aid.2004.20.1046
|View full text |Cite
|
Sign up to set email alerts
|

Rapid HIV Type 1 Testing of Women Presenting in Late Pregnancy with Unknown HIV Status in Lima, Perú

Abstract: We studied the feasibility and acceptability of HIV-1 testing using rapid serological assays in pregnant women presenting in late pregnancy without prior HIV-1 testing. Pregnant women presenting to the emergency room at the Instituto Materno-Perinatal in Lima, Peru, were offered on-site rapid HIV-1 testing. Consenting women were provided HIV counseling and had samples taken for rapid detection of antibodies in the blood and oral secretions. Women testing HIV-1 seropositive by one or both assays were offered st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 9 publications
0
13
0
Order By: Relevance
“…The impact of POC diagnostics on the target population, HIV-infected women, was not clearly defined in four studies (3134). One study was aimed at determining the feasibility and acceptability of HIV rapid tests in pregnant women presenting in late pregnancy without prior HIV testing (35). Two studies were aimed at determining the accuracy and performance of the diagnostics (36, 37).…”
Section: Resultsmentioning
confidence: 99%
“…The impact of POC diagnostics on the target population, HIV-infected women, was not clearly defined in four studies (3134). One study was aimed at determining the feasibility and acceptability of HIV rapid tests in pregnant women presenting in late pregnancy without prior HIV testing (35). Two studies were aimed at determining the accuracy and performance of the diagnostics (36, 37).…”
Section: Resultsmentioning
confidence: 99%
“…All remits of ethical principles involving human participants were followed for this study [19]. Informed written consent was obtained from all the participants (pregnant women and FLWs).…”
Section: Ethical Considerationmentioning
confidence: 99%
“…The number of false-positive determinations using HIV RTs has been surprisingly small even in low HIV prevalence populations where specificity would be expected to be reduced. International studies (USA, Peru, Thailand and India) have all shown HIV RTs specificities of 99.9% or greater in a population from antenatal clinics, sexually transmitted infection clinics and individuals having HIV occupational exposures [22][23][24][25][26][27]. The recent WHO report including ten HIV RTs tested on a wellcharacterized panel found specificities greater than 94.6% with four tests having 100% [28].…”
Section: Rapid Hiv Test Performancementioning
confidence: 99%
“…However, the combination of RTs in either serial or parallel algorithms improves the overall specificity and, in practice, few dual RT reactive/reference test-negative errors have been observed and it is unclear whether these are test or process related [24,31].…”
Section: Testing Algorithmsmentioning
confidence: 99%
See 1 more Smart Citation